Control of the periodical quantum echo of atom bit with arbitrary initial states in two-photon channel - Bing-ju ZHOU; Xiao-juan LIU; Jie ZHAN; Ren-long ZHOU (Tongxin xuebao)
By means of the full quantum theory,the conditions of generating a periodical quantum echo in the two-photon channel of a atom bit with arbitrary (pure or mixed) initial states was investigated,in coherent light field.Having studied the effects both the atom bit initial state and the surroundings parameter on its fidelity evolution,respectively,the parameter for control the periodical quantum echo of the atom bit was got and discuss its physical characters was discussed,that may be as a possible theoretical basis to the realization of a high fidelity output of quantum information.